Comparison of Intelligence based on Short-term Memory Test between Urban and Rural Children - Amira Addiniya; Leonardo Lubis; Marietta Shanti Prananta (Faculty of Medicine Universitas Padjadjaran, 2019)
Background: Cognitive development occurs during childhood and this development is influenced by various environmental factors such as urban and rural environments which can affect child cognitive development. Short-term memory is very important as the first step in processing new information to do cognitive tasks. The aim of this study was to compare the short-term memory of children coming from an urban and rural area.Methods: A cross-sectional design was performed in this observational analytical study, conducted from September to October 2014 in Jatinangor. Students from elementary school students in an urban and rural area in Jatinangor were selected, using a stratified random sampling method. The Digit Span Forward, Backward, and Symbol Digit Modality Test (SDMT) were used to measure short-term memory. Mann-Whitney test and independent T-test were used in this research.Results: There was no significant difference in Digit Span Forward score between urban and rural boys (p=0.564); and girls group (p=0.982). On the contrary, Digit Span Backward score among urban boys (p=0.007) and urban girls (p=0.006) was significantly higher compared to those living in the rural areas. Similarly, a significantly higher score of SDMT in the urban areas was found compared to rural for boys (p=0.011) and girls (p=0.026).Conclusions: Intelligence based on a short-term memory test, consisting of Digit Span Backward and Symbol Digit Modality Test, is higher in urban children compared to children in the rural areas.